Methods for ecological research on terrestrial small mammals - McCleery, Robert A., 1972- (Johns Hopkins University Press, 2021)
A comprehensive and invaluable resource, Methods for Ecological Research on Terrestrial Small Mammals is a must-have for any ecologist working on small mammals.